THE USE OF CHAIN STORY GAME TO IMPROVE STUDENTS’ SPEAKING SKILL AT SMP NEGERI 4 LUBUKLINGGAU - Fransisca, Agnes (LP3MKIL, 2025)
This study was aimed to determine the effect of using the Chain Story Game strategy on the speaking skills of seventh-grade students at SMP Negeri 4 Lubuklinggau in the 2025/2026 academic year. The research method used was a pre-experimental design with a single-group pre-test and post-test. The study sample consisted of 30 students selected through purposive sampling. The research instrument was a speaking test scored by two assessors based on aspects of grammar, pronunciation, vocabulary, fluency, and comprehension. Data were analyzed using a paired-sample t-test after testing for normality and reliability. The results showed that the average pre-test score was 57.36, with 20% of students achieving mastery, while the average post-test score increased to 78.43, with 83% of students achieving mastery. The t-test results showed a significant difference between the pre-test and post-test scores, with t-test > t-table. It can be concluded that the use of the Chain Story Game is effective in improving students' speaking skills. This strategy makes learning more interactive and enjoyable, and helps students gain confidence in speaking English, especially when practicing descriptive texts. Thus, the implementation of the Chain Story Game at SMP Negeri 4 Lubuklinggau was highly effective.